2014
DOI: 10.1590/s1806-37132014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Empyema and bacteremic pneumococcal pneumonia in children under five years of age

Abstract: We compared bacteremic pneumococcal pneumonia (BPP) and pneumococcal empyema (PE), in terms of clinical, radiological, and laboratory findings, in under-fives. A cross-sectional nested cohort study, involving under-fives (102 with PE and 128 with BPP), was conducted at 12 centers in Argentina, Brazil, and the Dominican Republic. Among those with PE, mean age was higher; disease duration was longer; and tachypnea, dyspnea, and high leukocyte counts were more common. Among those with BPP, fever and lethargy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Both the long duration of hospital stay (LOS) and the fact that 58% of children with PPE/PE required treatment in an intensive care unit confirm the severity of this disease. The median LOS of 17 (IQR [13][14][15][16][17][18][19][20][21][22][23][24] days is comparable to values reported from studies in Spain (17 days) 16 and Israel (15 days). 17 However, a number of other studies have reported shorter LOS for children with PPE/PE: A study in Brazil reported a median LOS of 11 days in 102 children; however, children with very severe pneumonia and signs of bacteremia were excluded.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Both the long duration of hospital stay (LOS) and the fact that 58% of children with PPE/PE required treatment in an intensive care unit confirm the severity of this disease. The median LOS of 17 (IQR [13][14][15][16][17][18][19][20][21][22][23][24] days is comparable to values reported from studies in Spain (17 days) 16 and Israel (15 days). 17 However, a number of other studies have reported shorter LOS for children with PPE/PE: A study in Brazil reported a median LOS of 11 days in 102 children; however, children with very severe pneumonia and signs of bacteremia were excluded.…”
Section: Discussionsupporting
confidence: 63%
“…The median LOS of 17 (IQR 13–24) days is comparable to values reported from studies in Spain (17 days) and Israel (15 days) . However, a number of other studies have reported shorter LOS for children with PPE/PE: A study in Brazil reported a median LOS of 11 days in 102 children; however, children with very severe pneumonia and signs of bacteremia were excluded . In a small prospective study with 18 patients by Kurt et al, children treated with pleural draining catheter and subsequently receiving intrapleural fibrinolytic therapy in their further course of disease had a mean LOS of 13 days compared to 6 days for children following initial VATS; the fact that the treatment was carried out in a highly specialized center may, together with the specific characteristics of the US health care system, offer a possible explanation for the considerably shorter LOS observed in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre los gérmenes productores de neumonías con derrame, el más frecuente en menores de 5 años sin factores de riesgo es el S. pneumoniae. 119 Con mucha menor prevalencia, se encuentra el S. aureus. Tal como se refirió en el apartado "Neumonía", la incorporación de la vacunación contra H. influenzae b al calendario oficial ha hecho que la prevalencia de microorganismos haya disminuido de manera muy significativa, y probablemente la vacuna antineumocócica también tenga influencia en la epidemiología de este germen en SPP en un futuro cercano.…”
Section: Epidemiologíaunclassified
“…Pyothorax is a purulent infection in which pathogenic bacteria invade the pleura or lymphoid tissue directly or indirectly, and the purulent exudate accumulated in the pleural cavity [4].There are many reports that the incidence of empyema in children is increasing [5][6] .Empyema mostly develops from pneumonia.The pathological process of pleural effusion can be divided into three stages: exudative stage, brous purulent stage and organizing stage.The mortality of empyema can be as high as 15% ~ 20% [7] .There is no uniform standard for the treatment of pleural effusion, and each stage of treatment focuses on different, which requires our clinicians to identify empyema in time, and strive to give timely and effective treatment in the shortest time.…”
Section: Discussmentioning
confidence: 99%